The Applications of the Principles of Ḥadīth and the Criticism of Sīrah Narrations - Saira Mehwash; Prof. Dr Humayun Abbas Shams (Journal of Religion and Society, 2026)
Across different periods, Sīrah writing has appeared in various styles and methodologies: traditional, historical, literary, and Ḥadīth-oriented. However, from the latter part of the twentieth century, a distinct trend of Ḥadīth-oriented Sīrah writing emerged. This trend emphasizes that every report related to the Prophet’s Sīrah ﷺ should be subjected to the same principles that the Muḥaddithūn established for the authentication of Ḥadīth Nabawī ﷺ. As a result, Sīrah studies shifted toward a new critical research methodology, with the primary objective of compiling a “Ṣaḥīḥ Sīrah of the Messenger of Allah ﷺ.” During the nineteenth and twentieth centuries, the academic world increasingly recognized that a foundational religious discipline such as the Sīrah of the Prophet ﷺ cannot be constructed upon ḍaʿīf Riwāyāt or unreliable historical statements. In the early period, when the events of Sīrah and Maghāzī were being compiled, the historical narrative approach predominated. Muʾarrikhūn documented the life events of the Prophet ﷺ, yet they generally lacked the rigorous methodology of Naqd al-Riwāyāt that later became the hallmark of Ḥadīth scholarship. In contrast, the Muḥaddithūn examined the events of the Sīrah in light of the principles of Isnād, Rijāl, Ittiṣāl al-Sanad, and ʿAdālah. Renowned Ḥadīth scholars such as Imām al-Bukhārī, Muslim, al-Nasāʾī, and al-Bayhaqī included dedicated chapters titled Kitāb al-Maghāzī in their compilations, presenting Sīrah-related reports with full Asānīd. In this way, Sīrah writing evolved into a well-protected scholarly discipline, emerging from the integration of both Riwayah and Dirāyah. Keywords: Ḥadīth-oriented, Sīrah writing, Naqd al-Riwāyāt, Muḥaddithūn